Natural Killer Cells in Asthma - Karimi, Khalil; Forsythe, Paul (Frontiers in Immunology, 2013)
The worldwide prevalence, morbidity, and mortality of asthma have dramatically increased over the last few decades and there is a clear need to identify new, effective, therapeutic and prophylactic strategies. Despite high numbers of NK cells in the lung and their ability to and generate a variety of immunomodulatory mediators the potential of these cells as therapeutic targets in allergic airway disease has been largely overlooked. The fact that IgE, acting through FcγRIII can activate NK cells resulting in cytokine/chemokine production implies that NK cells may contribute to IgE-mediated allergic responses. Indeed, current evidence suggests that NK cells can promote allergic airway responses during sensitization and ongoing inflammation. In animals models increased NK cells are observed in the lung following antigen challenge, while depletion of NK cells before immunization inhibits allergic airway inflammation. Moreover, in asthmatics NK cell phenotype is altered, and may contribute to promotion of the pro-inflammatory Th2-type environment. Conversely, driving NK cells towards an IFN-γ-secreting phenotype can reduce features of the allergic airway response in animal models. However, we have limited knowledge of the signals that drive the development of distinct subsets and functional phenotypes of NK cells in the lung and thus the role and therapeutic potential of NK cells in the allergic airway remains unclear. Here we review the potentially diverse roles of NK cells in allergic airway disease, identify gaps in current knowledge and discuss the potential of modulating NK cell function as a treatment strategy in asthma